Health and safety concerns related to CNT and graphene products, and related composites - Sousa, Susana P.B. (2020)
The use of Carbon Nanotubes (CNT) and Graphene increased in the last decade and it is likely to keep increasing in the near future. The attractiveness of their properties, particularly the possibility to enhance the composites performance using a tailor made methodology, brings new materials, processes and products for highly demanding industrial applications and to the market. However, there are quite a lot of health/safety issues, as well as lack of understanding and standards to evaluate their effects. This paper starts with a general description of materials, processes and products dealing with CNT and graphene. Then, an overview of concerns related to the health and safety when handling, researching, producing and using products that include these materials is presented. It follows a risk management approach with respect to simulation and evaluation tools, and considering the consensual limits already existing for research, industry and consumers. A general discussion integrating the relevant aspects of health and safety with respect to CNT and graphene is also presented. A proactive view is presented with the intention to contribute with some guidelines on installation, maintenance, evaluation, personal protection equipment (PPE) and personnel training to deal with these carbon-based nanomaterials in research, manufacture, and use with composite materials.